Indoor Air Quality Investigation at Primary Classrooms in Hamirpur, Himachal Pradesh, India - Shree, Venu; Marwaha, Bhanu M.; Awasthi, Pamita (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
Two schools in Hamirpur (Himachal Pradesh, India) having hybrid ventilation (ceiling fan) were selected for indoor and outdoor air quality investigation. Investigated parameters include temperature, relative humidity, CO2, and PM2.5 for both indoor and outdoor air quality. The average concentrations of CO2, and PM2.5 are estimated for indoor and outdoor air quality. Result shows that adopted building performance is not good in comparison with designed ones. The indoor concentrations of various pollutants are found to be higher in comparison with outdoor, so there is an urgent need to reduce the levels of pollutants inside the primary classrooms.